Jawi script and its contribution to the development of religious education in Terengganu, Malaysia - Fadzli, Adam; Daud, Ismail; Asyraf, Ab Rahman; Abdul Manan, Ali; Wan Ibrahim, Wan Ahmad (Serials Publications, 2017)
Jawi is an Arabic alphabetused for writing the Malay language and several other languages in Southeast Asia. Its importance stems from the fact that it has since been relegated to a script used for religious, cultural and administrative purposes amongst the Malay community in Malaysia. During the early stage of Islamisation period, the Arabic script was taught to the people who had newly embraced Islam in the form of religious practices, such as the recitation of Quran and other religious rituals. The Arabic script was later accepted by the Malay community together with their acceptance of Islam and they only took a short time to modify the script and adapt it to suit the spoken Classical Malay.This paper discusses the development of Jawi script and its contributions for religious educations in Malaysia particularly in the State of Terengganu. The discussion will revolve around famous works written by Malay religious scholars in Jawi writing and its’ impact upon religious understanding amongst the Malay community. Data for the study are gathered using qualitative method including analysis of old Jawi writings produced by the Malay scholars. Result shows that there are several religious works written in Jawi script which have a great impact on Muslims› religious understanding, besides preparing new generations for Islamic propagation within the community.